Removal of Illumination Gradient in TEM Images. Algorithm Implementation in TEM Imaging&Analysis Software - Zavodov, A. V. (Crystallography reports, 2021)
A method is proposed to solve the widespread problem in TEM imaging related to the illumination gradient. The illumination gradient is eliminated using line-by-line processing of the initial image in the 16-bit format and its transformation into an image with a narrower grayscale range [0–255]. The influence of image inhomogeneities on the processing result is eliminated using polynomial approximation of the initial values of average intensity of the lines and the width of intensity range ( ). The developed algorithm completely eliminates the illumination gradient in images by reconstructing details in the under- and overexposed regions and increasing the contrast of individual image parts. The entire code of the image-reconstruction algorithm for the TEM Imaging&Analysis software is presented.